Adrenocortical response to sepsis in insulin resistant animals - Caldareri, Lilian Julia (2019)
Adrenal insufficiency in patients with insulin resistance(IR) could affect the body´s response to stressful situations. Administrationof sucrose in the drinking water (DRS), to rodents, constitutes a valid modelfor human IR as it reproduces many of its characteristics. The aim of thepresent study was to analyze the HPA axis response in DRS-treated ratssubjected to a ligation and cecal puncture procedure (CLP), a very wellcharacterized sepsis model.Adult male Wistar rats were randomly distributed in sixgroups: Control, DRS, Control-Sham, Control-CLP, DRS-Sham and DRS-CLP. Rats inDRS groups received 30% sucrose for 15 weeks. IR was determined during the 10thweek by an insulin tolerance test. Sham or CLP surgeries were performed duringthe 15th week. For the following 24 hours before sacrifice, animalswere observed and body temperature was measured. Results indicate that surgery induces a significant increasein serum corticosterone levels in all groups (p<0.0001). Compared to Control-Sham, corticosterone levelswere higher in the C-CLP, DRS-SHAM and DRS-CLP groups (p<0.01) while only the DRS-CLP group showed higher circulatingACTH levels (p<0.01). Histologicalexamination of H&E stained tissues showedan area of ​​greater vascularization in the adrenal cortex of the DRS-CLP groupcompared to others. eNOS mRNA levels, as determined by RT-qPCR were higher inthe DRS-CLP group compared to others. In summary, regardless of circulating ACTH levels, DRS treatmentprevented the CLP-dependent increase in corticosteronemia. Taking into accountthe key role of glucocorticoids in the stress response, animals presenting anattenuated glucocorticoid output during sepsis may have a worse prognosis.